Genomic analysis of aggressive ductal adenocarcinoma of the prostate. (26th December 2022) - Kobayashi, Hiroaki; Kosaka, Takeo; Nakamura, Kohei; Kimura, Tokuhiro; Nishihara, Hiroshi; Oya, Mototsugu
Abstract: Background: Genomic profile analysis using next‐generation sequencing can potentially elucidate the pathogenesis of rare cancers. Ductal adenocarcinoma, a rare subtype of prostate cancer, has an aggressive nature. This is the first study to analyze the genomic profile of ductal adenocarcinoma in an Asian population. Methods: We identified 12 patients newly diagnosed with ductal adenocarcinoma of the prostate at two hospitals, and nine patients (75.0%) had the pure type. Genomic assessment was performed using either the PleSSision testing platform or FoundationOne CDx. Results: At least one genomic alteration occurred in 11 patients (91.7%), and the most frequently mutated gene was tumor suppressor protein p53 ( TP53 ), which was found in six cases (50.0%). Alterations characteristic of this cohort were found in four cases (33.3%) of retinoblastoma transcriptional corepressor 1 ( RB1 ), which was only observed in the pure type. Compared to previous study results, the frequency of genetic alterations in the phosphoinositide 3‐kinase (PI3K) pathway ( n  = 3; 25.0%) and Wnt‐β‐catenin pathway ( n  = 5; 41.7%) was comparable, but no alterations in the DNA damage repair (DDR) pathway were observed. None of the patients presented high tumor mutation burden or microsatellite instability. Conclusions: We found that the Asian cohort with ductal adenocarcinoma had actionable alterations, and a high frequency of alterations in TP53 and RB1 reflected the aggressive nature of the tumor. Genetic analysis using next‐generation sequencing is expected to help elucidate the pathogenesis of ductal adenocarcinoma. Abstract : This study is the first to analyze the genomic profile of ductal adenocarcinoma, that is a rare variant subtype of prostate cancer with an aggressive nature in an Asian population. We found that the Asian cohort with ductal adenocarcinoma was enriched for actionable alterations and a high frequency of alterations in TP53 and RB1 reflected its aggressive nature.